Sustained censorship in KZ (2026-03) (Kazakhstan) - Voidly (2026)
CRITICAL severity censorship detected in Kazakhstan. Confidence: 72%. Data sourced from OONI.
Censorship Incident ID: KZ-2026-0192
Keywords: censorship; KZ; censorship; critical